2013
DOI: 10.7555/jbr.27.20130030
|View full text |Cite
|
Sign up to set email alerts
|

The MDM2-p53 pathway revisited

Abstract: The p53 tumor suppressor is a key transcription factor regulating cellular pathways such as DNA repair, cell cycle, apoptosis, angiogenesis, and senescence. It acts as an important defense mechanism against cancer onset and progression, and is negatively regulated by interaction with the oncoprotein MDM2. In human cancers, the TP53 gene is frequently mutated or deleted, or the wild-type p53 function is inhibited by high levels of MDM2, leading to downregulation of tumor suppressive p53 pathways. Thus, the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
160
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(162 citation statements)
references
References 155 publications
(207 reference statements)
2
160
0
Order By: Relevance
“…Increasing numbers of RPs have been shown to play a part in regulating the p53–MDM2 pathway upon ribosomal stress (reviewed in 133). Several ribosomal proteins, including RPL5, RPL11, and RPL23, have been shown to interact with the MDM2 central acidic motif in a similar, yet distinct, manner.…”
Section: Mdm2 and Mdmx In Human Cancermentioning
confidence: 99%
“…Increasing numbers of RPs have been shown to play a part in regulating the p53–MDM2 pathway upon ribosomal stress (reviewed in 133). Several ribosomal proteins, including RPL5, RPL11, and RPL23, have been shown to interact with the MDM2 central acidic motif in a similar, yet distinct, manner.…”
Section: Mdm2 and Mdmx In Human Cancermentioning
confidence: 99%
“…p53 is kept at very low levels in normal cells and dramatically stabilized in response to a variety of stress signals, including DNA damage, abnormal oncogenic activation, and hypoxia (Harris and Levine, 2005;Kruse and Gu, 2009;Vousden and Prives, 2009). The stability of p53 is primarily regulated by its negative regulator murine double minute 2 (Mdm2), which binds p53 and functions as an E3 ubiquitin ligase leading to p53 ubiquitination and degradation (Haupt et al, 1997;Honda et al, 1997;Kubbutat et al, 1997;Nag et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetically inactivated RASSF10 has been suggested in diverse tumours, including prostate carcinoma, glioblastoma, skin malignant melanoma and thyroid cancer [11-14]. Previous findings have indicated that RASSF10 might suppress the growth of colorectal and hepatocellular carcinomas, as well as stimulate cell cycle arrest and cell apoptosis by activating p53 signalling [15-18]. The dominant components of p53 signalling, including p53, p21, Bcl-2 and Bax, have been extensively studied in carcinomas [16, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, the p53 mutation appears to be the most frequent genetic alteration observed in tumour cells. For instance, the mutated form of p53 regularly appears in undifferentiated thyroid carcinomas [20-22], and MDM2, another pivotal element of p53 signalling, can directly catalyse p53 degradation by exacerbating p53 ubiquitination [18, 23]. …”
Section: Introductionmentioning
confidence: 99%